Penerapan Arsitektur Perilaku Berhijab Dan Ukhuwah Islamiyah Pada Bangunan Pusat Kebugaran Dan Kecantikan Wanita Di Makassar - Chomaero, Zety; Marwati, Marwati; Andi Herniwati (TIMPALAJA : Architecture Student Journals, 2023)
Abstract_ Behavioral architecture is architecture whose implementation always includes behavioral considerations in design. Humans are the center of the environment and at the same time also become part of the environment. In general, the application of behavioral architecture contains elements that must be taken into account, including social activities that are accommodated in the building, the flexibility required for each activity, activities that influence or are influenced, and Background and goals of space users. Descriptive study identifying hijab behavior and Islamic brotherhood in the case of a design study for women’s fitness and beauty centers. The identification results found behavioral groupings in the form of private space zones for beauty care activities, fitness activities and semi-private activities in shared space zones such as commercial and information areas. Neutral colors are used in the room to make visitors safe and comfortable.